Products and processes in early foreign language learning - Mihaljević-Djigunović, Jelena (2008)
This paper focuses on the first stage of an exploratory study with Croatian first grade learners of English as a foreign language. The study is part of a longitudinal multinational project (ELLiE) in which the same investigations are carried in Croatia, England, Italy, Netherlands, Poland, Spain and Sweden. The sample (n=173) was drawn from city, small town and village settings. To get an insight into early language learning the authors looked into three sets of variables. Antecedent variables are represented by the wider social context (national foreign language education policy and characteristics of school setting), the language-learning milieu (perceived influence of significant others) and learner characteristics (ability and attitudes). Process variables refer to the immediate language learning environment comprising quality of instruction and out-of-class language exposure. Product variables are operationalised as listening, speaking and vocabulary task achievements, young learner linguistic self-confidence and end-of-the-year learner motivation. Data were collected by means of questionnaires, interviews, classroom observation and language tests. Analyses of the data for the three sets of variables and their subcomponents were carried out in order to determine their interactions. Both quantitative (means, correlations, regressions) and qualitative (observation and interview data analyses) approaches were applied. Comparisons were made with findings in the other contexts included in the ELLiE project. On the basis of the obtained results an attempt at interpreting the role of the included variables in early foreign language learning will be made.